Study of the damage characteristics and corrosion mechanism of tunnel lining in a sulfate environment - Liu, Xinrong; Zhuang, Yang; Zhou, Xiaohan; Liang, Ninghui; Mao, Jinwang; Chen, Hai (Frontiers in Materials, 2024)
Sulfate corrosion is one of the main reasons for the deterioration of tunnel lining. Accurate understanding of the damage characteristics and corrosion mechanism of the tunnel corroded by sulfate is the basis of the tunnel lining anti-corrosion design and damage control. Based on the project of a tunnel corroded by sulfate in the mountainous area of Southwest China, this research conducted field investigation and laboratory tests, and combined with existing research data, summarized the damage characteristics and corrosion mechanism of this kind of tunnel, finally proposed the characteristic corrosion state of tunnel lining under sulfate environment. The results show that: (1) The sulfate corrosion led to leakage, surface spalling crystallization and strength loss, and the arch waist and arch foot were typically where the corrosion occurs. (2) Both physical and chemical corrosion occurred in the tunnel lining, and the corrosion products included sodium sulfate, calcium carbonate, gypsum, ettringite and thaumasite. (3) In China, this kind of tunnel is mainly located in the Southwest China and Northwest China, and its lining is in a special state of “One-sided accelerated corrosion”.